Juvenilization in adult and youth education as a side effect of accountability policies - Pereira, Talita Vidal (2018)
This article analyzes the phenomenon called Juvenilization in Educação de Jovens e Adultos (EJA) [Adult and Youth Education] as a result of the exclusion of young people with age-grade discrepancy from regular school. The assumption is that the phenomenon has intensified, as the flow correction has worked as an escape mechanism used by managers to avoid the penalties prescribed in the accountability policies for schools and teachers not reaching the performance targets established for the different levels of the system. Statistical data about the EJA academic transcripts from the municipal school network of Rio de Janeiro are used to support the large-scale assessment policies. These policies, announced as guarantors of the quality of education, have favored the maintenance of school exclusion processes. Poststructuralist contributions, particularly Discourse Theory, support the problematizing of an instrumental concept of quality.